Deep medullary vein dysfunction is associated with cerebral microbleeds in cerebral small vessel disease - Lan, Haiyuan; Lei, Xinjun; Xu, Zhihua; Yu, Jie; Wang, Huimei (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study investigated the association between deep medullary vein (DMV) dysfunction and the development of cerebral microbleeds (CMB) in patients with cerebral small vessel disease (CSVD), with a particular focus on the contribution of extracellular fluid accumulation.MethodsThis was a cross sectional study. Clinical and imaging data from 176 patients with CSVD were consecutively collected between July 2024 and May 2025. DMV visibility was scored on a scale of 0–18 using susceptibility-weighted imaging (SWI). CMB were quantified on SWI magnitude images and categorized into three groups: absent CMB, mild CMB (1–2 lesions), and extensive CMB (≥3 lesions). Extracellular fluid volume was estimated using free water (FW) values derived from diffusion tensor imaging. Associations between DMV scores, FW values, and CMB burden were evaluated.ResultsDMV scores were moderate positively correlated with both CMB burden and FW values (r = 0.460, P < 0.001; r = 0.549, P < 0.001, respectively), as well as between FW values and CMB burden (r = 0.561, P < 0.001). Patients in the extensive CMB group had significantly higher DMV scores and FW values compared to those in the absent CMB and mild CMB groups. Mediation analysis demonstrated that FW acted as a partial mediator in the relationship between DMV scores and CMB burden (β = 0.088, 95% CI: 0.048–0.152, P < 0.05). This mediating effect remained statistically significant after adjusting for age, sex, hypertension, diabetes, smoking, and hyperlipidemia (β = 0.054, 95% CI: 0.022–0.107, P < 0.05).ConclusionDMV dysfunction is positively associated with CMB burden in CSVD, partially mediated by increased extracellular fluid accumulation. These findings suggest that impaired venous drainage and interstitial fluid retention may play a role in the pathogenesis of CMB.